Academic-Community Partnerships: Effectiveness Evaluated Beyond the Ivory Walls - Rosemary M. Caron; Jessica D. Ulrich-Schad; Catherine Lafferty (The University of Alabama, 2022)
Community-based participatory research (CBPR) has furthered our understanding of the working principles required for academic-community partnerships to address persistent public health problems. However, little is known about how effective these partnerships have been in eliminating or reducing community-based public health issues. To contribute to the literature in this area, the authors conducted a survey of U.S. schools and programs in public health and community groups working with these academic partners to: (1) identify the most common local public health issues addressed; (2) examine the characteristics of the partnership and the actual or perceived benefits and challenges for each partner; (3) assess the perceived effectiveness of the partnership and their evaluation techniques; and (4) analyze the intent to continue or dissolve the partnership and the associated factors that influence this decision. The authors provide recommendations that can improve the development, functioning, and effectiveness of academic-community collaborations aimed at addressing a variety of public health concerns.